Analysis of Sales Ratio Assessment as a Test Tool for Accuracy of Determination of Tax Object Sales Value against Market Value Case Study In Kabandungan Village - Anshor, Mohamad Akbar Akmala; Ismatullah, Ismet; Sofiani, Venita (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to analyze the determination of the Tax Object Sales Value (NJOP) for land and buildings in Kabandungan Village, Kabandungan District, and examine the conformity of NJOP with market values. The method used is the Assessment Sales Ratio (ASR) which refers to the provisions established by the Directorate General of Taxes and the International Association of Assessing Officers (IAAO). Primary data was obtained from the Tax Office Pratama Kabupaten Sukabumi and the Kabandungan Village Office. The analysis results indicate variations in the level of conformity between NJOP and market values among the different hamlets in Kabandungan Village. While some hamlets achieve a good level of accuracy, others still fall short of the established standards. Therefore, it is recommended to review the ASR method, conduct further studies on factors influencing NJOP determination, improve coordination among relevant institutions, update and maintain accurate data, and implement training and capacity building in property assessment. This research contributes to understanding and improving the NJOP determination process in Kabandungan Village.